THE IMPORTANCE OF NAMES IN T. S. ELIOT’S POETRY - Nurlana Akhundova (International Journal of Innovative Technologies in Social Science, 2020)
Names are of great importance in Thomas Stearns Eliot’s poetry. He chooses titles to provide a general overview of a particular poem. The author used a variety of names in his literary activity to intrigue the reader’s curiosity. In this article, we will discuss the titles related to musical terms. Here proper names will be analyzed in detail. Names the poet utilizes in his poetry are of different origins: some of them are mythological heroes, others are formed just by combining the letters, and some are acquaintances or place names. Due to T. Eliot’s conversion, the naming of personages underwent a religious transformation. The character names with negative meanings preoccupy his early poems. They are associated with animals who only rely on their basic instincts, the living deads who only exist physically, infertile and unloving creatures that betray each other. After changing of faith, he added Christian names to power his poetry. We will lay stress on the formation, usage, relation of titles, and analyze how they identify the poetry.